(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
When we are discussing problems which have an easy space of possible solutions to know, our search is reduced to find an optimal (A high point or a mínimum point ) which gives a solution to the problem once some restrictions were given. However there are complex problems of combinatorial optimization at various fields like economy, the commerce, the engineering, re-engineering of software, communications, the industry or the medicine, the fact that often they are very difficult from resolving in practice and whose mathematical modeling Formulated coherently it does not allows a solution with the analytical tools near by the hands. Because of that testing the actual complexity generated in the institutions and business world, as the diversity in the phases in which de process of institutional change develops, it becomes necessary the development and use of methods that allow the management of problematic situations from the set of its parts and also from different point of views. Because of that low performance of the exact algorithms for many problems, there has been developed multiple types of approximated algorithms, that provides high quality solutions for this combinatorial problems (though not necessarily the optimal) in a short computational time, these algorithms include the denominated heuristics techniques and metaheuristics.